Three new species of Duplicibothrium (Cestoda: 'Tetraphyllidea') from cownose rays in Senegal with a phylogenetic analysis of the genus. (2nd February 2022) - Stephan, Douglas; Caira, Janine N.
Abstract: Three new species of 'tetraphyllideans' in the family Serendipeidae are described from cownose rays off Senegal. Duplicibothrium jeannettae n. sp. and Duplicibothrium collosum n. sp. parasitize both Rhinoptera marginata and Rhinoptera peli . Duplicibothrium jillae n. sp. parasitizes R. marginata . Duplicibothrium jeannettae n. sp. and D. jillae n. sp. differ from one another and their described congeners in size, number of proglottids, and locular configuration. The generic assignment of D. collosum n. sp. was initially unclear because its scolex more closely resembles that of Serendip than Duplicibothrium . To help inform generic placement, sequence data were generated for the 28S rDNA gene (D1–D3 region) for the three new species as well as for Duplicibothrium minutum and Duplicibothrium n. sp. 2 from Rhinoptera bonasus off North Carolina, Duplicibothrium n. sp. 3 from Rhinoptera brasiliensis off Belize, Duplicibothrium n. sp. 4 and Duplicibothrium n. sp. 5 from Rhinoptera jayakari off Mozambique, and Duplicibothrium n. sp. 6 from Rhinoptera neglecta off Australia. Comparable data were obtained from GenBank for adults and larvae of Duplicibothrium collected from the Gulf of Mexico. The tree resulting from a maximum likelihood analysis (MLA) placed D. collosum n. sp. robustly within Duplicibothrium ; the generic diagnosis is emended accordingly. This raises a question regarding the independence, and thus also validity, of the three genera of the Serendipeidae – a question that must await a molecular analysis that includes Serendip and Glyphobothrium . These results extend the hosts of Duplicibothrium to include R . brasiliensis, R . jayakari, R . marginata, R . neglecta and R . peli, and the distribution to include the western Pacific Ocean, eastern Atlantic Ocean, and western Indian Ocean (Zoobank Registration: 97BB5020-BFFF-4FEA-AE07-B4711D1110FC).